Gender Differences of Achilles tendon Cross-sectional Area during Loading - Intziegianni, Konstantina; Cassel, Michael; Hain, Gerrit; Mayer, Frank (Sports Medicine International Open, 2017)
The Achilles tendon (AT) is larger and stiffer in males compared to females. AT stiffness is determined by length differences during loading. However, as some collagen fibres run transversely, changes in cross-sectional area (CSA) are also expected. The study investigates the gender differences of AT-CSA during maximal voluntary isometric contraction (MVIC).Fifteen males and fifteen females were positioned prone on the isokinetic dynamometer with knee extended and ankle flexed 90°. AT-CSA [mm2] from rest to MVIC during plantar flexion was sonographically assessed. AT-CSA maximal deformation [mm2] was subtracted by CSAMVIC–CSArest. AT-CSA compliance [mm2/Nm] and strain [%] were calculated by dividing the CSA deformation [mm2] by peak torque [Nm] and CSA at rest [mm2], respectively. Gender differences were assessed by an independent sample t-test with Bonferroni correction (α=0.01).AT-CSA dimensions at rest (p=0.001) and contraction (p=0.001) as well peak torque (p=0.001) were statistically significant higher in males (54.4±5.1 mm2, 53.7±5.1 mm2, 120.1±26.8 Nm) compared to females (46.2±7.0 mm2, 43.4±6.9 mm2, 86.9±21.6 Nm). AT-CSA deformation (p=0.000) strain (p=0.000) and compliance (p=0.000) were found to be statistically significant higher in females (–2.8±0.9 mm2, –6.2±2.0%, –0.033±0.018 mm2/Nm) compared to males (–0.8±1.8 mm2, –1.4±3.3%, –0.007±0.008 mm2/Nm).During loading, the AT also deforms at the transverse level by reducing its CSA. CSA reduction was higher in females, indicating also higher CSA compliance compared to males. Higher CSA compliance might indicate higher adaptability towards loading and might be discussed as a protective factor.
Keywords: Achilles tendon; reliability; cross-sectional area; compliance; strain; gender